Titan’s organic chemistry: A planetary-scale laboratory to study primitive Earth - Athena Coustenis (Mètode Science Studies Journal: Annual Review, 2016)
Saturn’s largest satellite, Titan, has been revealed by extended ground-based and space observations, and recently by the Cassini-Huygens mission. Titan’s atmosphere hosts a complex organic chemistry in the solar system starting with nitrogen and methane and leading to the formation of hydrocarbons and nitriles, including prebiotic molecules. The atmosphere also contains traces of oxygen compounds. This system is subject to seasonal variations and different physical, dynamic, and photochemical processes. Interactions between the atmosphere, the surface, and the interior also play an important role in the astrobiological potential of the satellite.